Perlindungan Hukum Notaris Terhadap Perjanjian Perikatan Jual Beli yang Diikuti Dengan Adanya Pengakuan Hutang - Ivan Chairunanda Kusuma Putra (Universitas Islam Indonesia, 2018)
This study aims to determine the objective legal conditions in the sale and purchase agreement made by a notary for the purpose of recognition of debt, with the following problem formulation: How does the legal protection of the notary in the drafting of the sale and purchase agreement for the purpose of recognition of debt? What is the validity of the sale and purchase agreement, and the responsibilities of the parties if there is one party that is in default? This research is an empirical legal study, in which the data is collected through interviews with Notaries in Yogyakarta City, and the results are presented in the form of descriptions and opinions. The analysis was carried out using a statutory approach combined with facts obtained from interviews. The results show that legal protection for notary deeds of sale made for the benefit of debts and debts still has many weaknesses: formal legal rules that do not fully protect the rights of the parties, such as the absence of legal force on the deed if there is default; there is also the possibility of canceling the deed, because the deed of sale and purchase agreement with the deed of accounts payable is separated, so it is not in accordance with the provisions of the relevant act. In this study, the authors recommend to the parties to always prioritize their respective rights and obligations according to the law, so that the deed has the same legal force.